Association of Acute Coronary Syndromes with Blood Groups: A Single-Center, Observational Study - Mohammed Rehan Omar Siddiqi, Adnan Ghafoor, Muhammad Asim Rana, Salman Shakeel, Jahanzeb Kamal, Ali Nasir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Evidence suggests an association between ABO blood groups and cardiovascular diseases; particularly acute coronary syndromes, a major reason for hospitalization and mortality. Aim: To investigate the association between ABO blood groups and acute coronary syndrome (ACS) frequency. Study design: Cross-sectional study. Place and duration of study: United Hospital, Karachi from 1st June 2022 to 31st December 2022. Methods: Two hundred and five participants with a diagnosis of ACS were enrolled in this study. A structured questionnaire was used to gather the data regarding the demographics and clinical characteristics of the patients. By utilizing specific antibodies and the agglutination approach, blood types were identified. ECG, coronary angiography, echocardiography and troponin-I were performed on these patients. Results: Blood groups B+ and O+ among ACS patients had the largest prevalence (35.1 and 28.8%, respectively) and there was a significant association between blood groups and the type of MI (p=0.008). The most frequently diagnosed MI was anterior wall myocardial infarction (AWMI), which is highly prevalent among patients with the type A (+ve) blood group. Moreover, the risk factors were equally prevalent among patients of different blood groups. Conclusions: The frequency of ACS and ABO blood type were significantly correlated and there was no statistically significant correlation between any risk factors under study and blood type. Keywords: Acute coronary syndrome, ABO blood type, Risk factors